Robot Lawyers and the Ethical Challenges of the Legal Profession in the Era of Artificial Intelligence - Setyawan, Vincentius Patria (Balobe Law Journal, 2025)
Introduction: The ethical dilemma that arises due to the integration of artificial intelligence into legal services through the emergence of robot lawyers.Purposes of the Research: The purpose of this article is to examine the ethical implications of robot lawyers and evaluate the adequacy of current legal professional standards in addressing challenges posed by artificial intelligence in legal practice.Methods of the Research: This study uses normative legal research with a conceptual and statutory approach, focusing on the analysis of existing legal ethics frameworks and professional responsibility principles to assess their relevance and adequacy in regulating the use of artificial intelligence in legal practice.Results of the Research: The findings of this study show that the emergence of robot lawyers significantly challenges the ethical foundations of the legal profession, particularly concerning competence, confidentiality, independence, and accountability. Current legal ethics frameworks were designed with human practitioners in mind, leaving regulatory gaps when applied to AI-driven legal services. The study highlights the need for a revised ethical paradigm that addresses the limitations of existing rules and accommodates the unique attributes of artificial intelligence. The novelty of this research lies in its critical analysis of the intersection between legal ethics and AI technology, offering a conceptual framework for ethical governance of robot lawyers.